Is addressing violence against women prioritised in health policies? Findings from a WHO policies database. - Eva Burke; Katherine Watson; Gillian Eva; Judy Gold; Claudia Garcia-Moreno; Avni Amin (Public Library of Science (PLoS), 2024)
Violence against women (VAW) affects almost 1 in 3 women and can lead to short and long-term adverse health outcomes. The health sector is an important entry point to respond to VAW. Globally, countries have committed to eliminating VAW through the SDGs and WHO Member States have endorsed a Global Plan of Action on Violence, which asks countries to provide comprehensive health services to VAW survivors. To track progress and establish a baseline for the Global Plan of Action on Violence, WHO developed a VAW Policies Database to assess how countries are addressing VAW in health and multisectoral policies. This paper presents findings from 15 select indicators related to the existence of VAW-related policies and the inclusion of health services for survivors in policies in line with WHO recommendations. Results show that while 80% of countries have multisectoral VAW policies in place, only 34% have national health policies that include VAW response and/or prevention as a strategic priority, and 48% have clinical guidelines for the health sector response. Policies were analysed to identify inclusion of WHO-recommended VAW health services: 75% of countries' policies mention provision of first-line support; while 50% or fewer of countries mention clinical enquiry to identify intimate partner violence, post-rape care services, or mental health assessment, referral and treatment. The high-income countries group had the lowest proportion of countries that specified each of the above-mentioned health services in policies. Findings show that more efforts are needed to raise the awareness of ministries of health about the public health impact of VAW and the importance of including VAW in health policies. Where policies exist, many are not aligned with WHO-recommendations. Policy dialogues should be conducted with governments on how to better align their VAW policies with internationally-agreed, evidence-based standards, and to implement them through programmes and services.